1999
DOI: 10.2337/diabetes.48.6.1217
|View full text |Cite
|
Sign up to set email alerts
|

Activators of peroxisome proliferator-activated receptor-alpha induce the expression of the uncoupling protein-3 gene in skeletal muscle: a potential mechanism for the lipid intake-dependent activation of uncoupling protein-3 gene expression at birth.

Abstract: The recently identified uncoupling protein-3 (UCP-3) gene, predicted to encode a new member of the family of uncoupling proteins, is preferentially expressed in skeletal muscle and has been related to phenotypes of obesity and type 2 diabetes. We have established that during mouse ontogeny, the expression of the UCP-3 gene is switched on in skeletal muscle just after birth. The induction of UCP-3 gene expression is dependent on the initiation of suckling and particularly on lipid intake. Treatment of newborn m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
82
0
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(93 citation statements)
references
References 26 publications
(38 reference statements)
9
82
0
2
Order By: Relevance
“…Fatty acids themselves when administered in vivo induce UCP3 gene expression in both rodents and humans (18,19). Altogether, these data favor the hypothesis that the primary function of UCP3 in skeletal muscle may be to either passively or actively regulate the utilization of lipids as a fuel substrate.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…Fatty acids themselves when administered in vivo induce UCP3 gene expression in both rodents and humans (18,19). Altogether, these data favor the hypothesis that the primary function of UCP3 in skeletal muscle may be to either passively or actively regulate the utilization of lipids as a fuel substrate.…”
supporting
confidence: 62%
“…Multiple hormonal treatments in vivo, such as leptin, thyroid hormones, glucocorticoids, and especially peroxisome proliferator-activated receptors agonists, cause dramatic changes in UCP3 gene expression in muscle (14) (18). Although studies have been carried out on the UCP3 promoter (20), the hormonal signals and responsive elements regulating UCP3 gene transcription in skeletal muscle have not yet been identified.…”
mentioning
confidence: 99%
“…In itro and in i o experiments demonstrated that fatty acids or certain retinoids promote UCP2 and\or UCP3 expression in white and brown adipocytes, myocytes and pancreatic islets [171,172,177,206,[229][230][231][232][233][234][235][236][237][238]. Expression of UCP2 and\or UCP3 in skeletal muscles, heart or adipose tissue can be induced by various situations characterized by elevated levels of circulating non-esterified fatty acids, such as starvation in humans or rodents [84,169,239,240], high-fat feeding in rodents [30,177] and genetic or experimental diabetes in rodents [31,241,242].…”
Section: Contribution Of Ucps To Dit Energy Partitioning and Lipid Mmentioning
confidence: 99%
“…injection of 50 mg/kg body weight, we cannot categorically exclude the possibility that there may be some additional activation of PPAR and/or PPAR . Rats were sampled at 24 h after WY14,643 administration (Brun et al 1999), thereby avoiding the long-term effects of PPAR activation to deplete visceral adipose tissue (Ye et al 2001). Food intake was not influenced by WY14,643 administration in either the CON or HIFAT rats (results not shown).…”
Section: Animalsmentioning
confidence: 99%